Humoral immune response to four SARS-CoV-2 vaccines in healthcare professionals - Pareja Cruz, Arturo (2022)
Objective: To describe the concentration of neutralizing antibodies in serum from healthcare professionals who received any of the SARS-CoV-2 vaccines developed by Sinopharm, Pfizer or Johnson & Johnson, or CureVac’s vaccine candidate. Materials and methods: An observational, descriptive, retrospective, cross-sectional research which included 217 healthcare professionals fully vaccinated with Sinopharm, Pfizer or Johnson & Johnson’s vaccines, or CureVac’s vaccine candidate. The presence of anti-SARS-CoV-2 neutralizing antibodies in serum was determined in these individuals using the electrochemiluminescence immunoassay (ECLIA). Variables such as age, sex, history of infection with SARS-CoV-2, concentration of neutralizing antibodies and brand of vaccine administered were considered. Results: Sixteen point six zero percent (16.60 %) of the healthcare professionals stated that they had already had COVID-19 before receiving the vaccine. They were immunized with the vaccines developed by Sinopharm (74.65 %), Pfizer (12.90 %) or Johnson & Johnson (5.07 %), or CureVac’s vaccine candidate (7.37 %). Regardless of the vaccine received, 42.50 % of the individuals who had not been previously infected with SARS-CoV-2 and 16.70 % of those who had been previously infected did not develop neutralizing antibodies. Pfizer’s vaccine produced the highest concentration of neutralizing antibodies (196.27 AU/mL) in patients with or without previous infection. Conclusions: The study demonstrates that vaccination boosts immunity in people previously infected with the novel coronavirus and suggests that Pfizer’s vaccine produces the highest concentration of neutralizing antibodies.